Penetrating facial trauma from a Taser barb. Issue 2 (February 2019) - Campbell, F.; Clark, S.
Abstract: The Taser X26 ® (Axon) is a conducted energy device that is used by the police forces in the United Kingdom to deliver a high voltage shock that will disable a person. Injuries related to its use are uncommon but can be serious, the extent of the damage caused being related to the structures targeted and the length of deployment of the electrical charge. We describe a 15-year-old boy who had a penetrating midfacial injury after deployment of a Taser, the barb of which became embedded in the subtarsal region of his left cheek. Removal under general anaesthetic was uncomplicated, and exploration of the wound showed that there was no damage to adjacent structures. Case reports of this type are limited, and we know of none of a penetrating injury of the midface.